Peningkatan penanggulangan penyakit demam berdarah dengue berbasis masyarakat dengan punyuluhan kesehatan - Paiman Soeparmanto, Setia Pranata (Berita Kedokteran Masyarakat (BKM), 2006)
Backgrounds: Dengue Disease Fever (DDF) causes of Dengue Virus and contagious mosquito bite Aedes Aegypti. Overcoming problem expanding of Dengue Disease Fever have been done through direct health education by health worker and through media printing and electronic, but still obtained more occurrence Dengue disease, especially in the big towns. Therefore needed health education development which can was done by self's community. From this background the objective of research is learning improvement of the prevention to DDF with health education on the community based. Methods: Research design is quasi - experimental design pre and post test use control group. lntervence is: first train the health cadres, Chief Rukun Telangga (RT) and Chief Rukun Warga (RW) to implementation health education of DDF, Every family was given leaflet and sticker as overcoming DDF briefing. Data collecting was conducted with closed questionnaire and data analyses are T-Test and Chi square. This considering obtained data having the character of interval and categories. Results: Result of research that mostly respondent old age than 41 year, most have level education SLTP above and it's most merchant 20% and the other is farmer. PNS/ABRI, and private sector officer. Age group, and education level respondent not significant different between study and control area, and the work's respondent significant different between the study and control area. To get information about Dengue Disease directly, most from neighbor what is obtained by join to feel and partly. minimize through health worker, and urban leader formal (Kalurahan Pamong), Health Cadre and Chief of RT/RW. Most media which a lot of weared obtaining dengue disease information by respondent through TV 60%, at the study and control area. While using leaflet relative minimize after health education and also before intervention especially in the study area. The knowledge level in the pre research at the study and the control area not significant different (p>0,05) namely mean value 16 (range 0-100), but in the post research the knowledge level more high in study area than in the control area. The pre research the behaviors of prevention of Dengue diseases not significant different between the study and control area (p>0.05), mean value 23 in the study and 24 in control area. At the post research prevention to behavior DDF between study and control area also not significant different (p>0,05). Conclusion: The level of knowledge and behavior prevention DDF increasing in the study and control in pre and post intervention. But mean value increasing of knowledge in study area more high was compared with in the control area. And mean value the increasing of behavior to overcoming DDF but not significant different between study and control area pre and post intervention. This situation causes health education on community based not yet were conducted by Health Cadre, Chief RT/RW, Kalurahan Pamong, and leaflet also sticker not yet was learned by family especially in study area. Keywords: dengue disease fever: health education